1999
DOI: 10.1177/0148607199023006337
|View full text |Cite
|
Sign up to set email alerts
|

Total Parenteral Nutrition Alters Molecular and Cellular Indices of Intestinal Inflammation in Neonatal Piglets

Abstract: These data identify molecular and cellular indices of intestinal inflammation that are responsive to IV feeding in neonates and provide a novel framework to investigate mechanisms underlying gut atrophy during TPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 29 publications
5
26
1
1
Order By: Relevance
“…IELs are the first immune cells to be exposed to foreign antigens and have the potential to be critical in host defense. A previous experiment in neonatal piglets demonstrated increased cytotoxic T lymphocytes in the lamina propria as well as increased GCs, implying that inflammation may play a role in the pathogenesis of TPNassociated mucosal changes (19). In addition, Li et al (34) found that lymphocytes play an important role in the regulation of mucosal immunity in a mouse model.…”
Section: Intestinal Permeabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…IELs are the first immune cells to be exposed to foreign antigens and have the potential to be critical in host defense. A previous experiment in neonatal piglets demonstrated increased cytotoxic T lymphocytes in the lamina propria as well as increased GCs, implying that inflammation may play a role in the pathogenesis of TPNassociated mucosal changes (19). In addition, Li et al (34) found that lymphocytes play an important role in the regulation of mucosal immunity in a mouse model.…”
Section: Intestinal Permeabilitymentioning
confidence: 96%
“…TPN not only reduces the population of enterocytes but also has been associated with expansion of mucosal goblet cells (GCs) and some lymphocyte subtypes (11,30). Furthermore, newborn (11,19) and adult (17) animal studies indicate that TPN-induced activation of lymphocytes may induce mucosal inflammation on the basis of increased ICAM-1 expression and myeloperoxidase activity. Studies in TPN-fed mice demonstrated that increased expression of the proinflammatory cytokine INF-␥ in activated intraepithelial lymphocytes (IELs) is linked to increased apoptosis and may contribute to the breakdown of epithelial barrier integrity (26,63).…”
mentioning
confidence: 99%
“…Immune responses to harmless dietary components must be regulated to prevent tissue damage and impaired absorption of macromolecules, and systemic tolerance to fed proteins ("oral tolerance") has been demonstrated in the pig [3,40]. Depending on the food composition and on the presence of oral food components the morphology of both the intestinal mucosa and the intestinal immune cells changes [15,30,36,37]. Thus, the immunological structures associated with gastrointestinal tract have evolved to generate different types of response to pathogens and to harmless environmental antigens.…”
Section: Gut Function and Immunitymentioning
confidence: 99%
“…Walsh et al (2012) also observed a slight effect of BT corn on the number of goblet cells in the small intestine. A twofold increase in goblet cells numbers in the small intestine of pigs as a result of total parenteral nutrition was correlated with a change in gut microbiota, reduced integrity of the mucosal barrier and increased inflammation of piglets (Ganessunker et al, 1999;Mair et al, 2010). Intestinal inflammation is accompanied by deepening of the intestinal crypts, shortening or even disappearance of the Control = non-transgenic near-isoline corn; BT-799 = transgenic corn produced by the insertion of the mCry1Ac gene derived from Bacillus thuringiensis strain; CC-2 = transgenic corn produced by the insertion of the maroACC gene derived from Agrobacterium tumefaciens strain; reference = corn from commercially available non-transgenic varieties.…”
Section: Discussionmentioning
confidence: 95%